Implementing primary healthcare nurse practitioners in long‐term care teams: A qualitative descriptive study. (24th March 2019) - Kilpatrick, Kelley; Jabbour, Mira; Tchouaket, Éric; Acorn, Michelle; Donald, Faith; Hains, Sylvie
Abstract: Aim: To identify the conditions needed to implement nurse practitioners (NP) in long‐term care (LTC) in Québec, Canada. Design: A qualitative descriptive study was undertaken. Methods: Semi‐structured interviews ( N  = 91) and socio‐demographic questionnaires were completed with providers and managers from May 2016–March 2017. Nurse practitioner activity logs were compiled at three sites. Content analysis was used. Results: All sites initially implemented a shared care model but not all sites successfully implemented a consultative model. The progression was influenced by physicians' level of comfort in moving towards a consultative model. Weekly meetings with physicians and nurse managers and an office for NPs located near healthcare teams facilitated communication and improved implementation. Half‐time NP positions facilitated recruitment. Improvements were noted in timely care for residents, family involvement and quality of documentation of the healthcare team. Regulatory restrictions on prescribing medications used frequently in LTC and daily physician presence at some sites limited implementation. Conclusion: The project fostered an understanding of the conditions needed to successfully implement NPs in LTC. An examination of the perspective of residents and families is needed. Abstract : 目的: 确定在加拿大魁北克省实施执业护士(NP)长期护理(LTC)所需的条件。 设计: 进行定性的描述性研究。 方法: 从2016年5月至2017年3月, 对供应商和管理者进行半结构式访谈( N = 91)和社会人口问卷调查。在三个站点汇编了执业护士活动日志。采用了内容分析法。 结果: 所有站点最初都实施了共享护理模式, 但并非所有站点都成功实施了咨询模式。医生在转向咨询模式时的舒适度会影响病情的进展。与医生和护士经理的每周会议, 以及位于医疗团队附近的执业护士办公室促进了沟通并改进了咨询模式的实施。临时执业护士职位有助于招聘。在住院医生的及时护理、家庭参与和医疗团队的文件质量方面都有所改善。长期护理中常用处方药物的监管, 以及在一些实施受限的站点中医师日常出诊都受到了限制。 结论: 本项目有助于理解在长期护理中成功实施执业护士所需的条件。需要审查居民和家庭的观点。